2022
DOI: 10.1155/2022/3534783
|View full text |Cite
|
Sign up to set email alerts
|

Male Gender Is Associated with Lymph Node Metastasis but Not with Recurrence in Papillary Thyroid Carcinoma

Abstract: Background. The incidence of papillary thyroid carcinoma (PTC) is higher in females than in males, but it remains unclear whether gender is associated with the aggressiveness of this disease. We aimed to clarify the influence of gender on the risk of developing lymph node metastasis (LNM) and on the prognosis of PTC patients. Study Design. Retrospective cohort study. Setting. Academic tertiary care center. Methods. Clinical data of PTC patients who were admitted to the Department of Endocrine and Breast Surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
3
3
0
Order By: Relevance
“…This is consistent with a recent study that also showed a negative correlation between age and CLNM, despite different age group cutoffs (15). Our study also revealed a higher CLNM detection rate in males, which is consist with the observations of Zhu et al (16). The negative correlation in females may be related to hormonal and reproductive factors (17).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with a recent study that also showed a negative correlation between age and CLNM, despite different age group cutoffs (15). Our study also revealed a higher CLNM detection rate in males, which is consist with the observations of Zhu et al (16). The negative correlation in females may be related to hormonal and reproductive factors (17).…”
Section: Discussionsupporting
confidence: 93%
“…Our study also revealed a higher CLNM detection rate in males, which is consist with the observations of Zhu et al. ( 16 ). The negative correlation in females may be related to hormonal and reproductive factors ( 17 ).…”
Section: Discussionsupporting
confidence: 93%
“…Aligning with Mao et al ’s meta-analysis ( 14 ), our study reaffirms male sex as a risk factor for LLNM in T1 stage PTC patients, highlighting a higher propensity for LLNM in men. This gender-based disparity in LLNM incidence aligns with several studies ( 15 , 33 ), although it remains a subject of debate in other research ( 34 , 35 ). Notably, the adverse prognosis associated with PTC tends to be more pronounced in men, despite its higher prevalence in women ( 36 ).…”
Section: Discussionsupporting
confidence: 86%
“…Thus, a great deal of research has been conducted to investigate the various risk factors associated with LN metastasis in PTC. Several risk factors significantly associated with LN metastasis in patients with PTC were identified in previous studies, including male gender, younger age, larger tumor size, multifocality, ETE, and lymphovascular invasion [14][15][16][17][18]. The identification of these risk factors facilitates the development of effective screening, diagnosis, and treatment strategies for patients with PTC at risk of LN metastasis.…”
Section: Discussionmentioning
confidence: 93%